(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Tobacco smoking is still a significant cardiovascular disease warning element and the top preventable death cause globally. The negative consequences of cigarette smoking and coronary heart problems are greater than initially assumed. The formation and advancement of heart problems, cardiac arrhythmia, including endothelial dysfunction, along with ischemic cardiovascular disorders, ought to be of special concern to physicians treating tobacco users. An emerging problem is the increasing usage of heat-not-burn cigarettes as a substitute for cigarettes. Changing how tobacco is delivered does not eliminate its negative consequences. For this particular research work, the researcher chose the impact of smoking on coronary heart disease as the research topic. The introductory part defined that coronary heart disease and tobacco consumption increase the risk of such disorders. The literature review part assessed the impact of tobacco smoking, passive smoking and smokeless tobacco on coronary heart diseases. The secondary research analysis is chosen as the research methodology for this particular work. In the result and recommendation parts, the researcher discussed how smoking affects blood pressure and cerebral blood flow along with the suggestive measures to prevent the smoking habits of the population. A significantly higher incidence of coronary heart problems including stroke is associated with a daily smoking habit of merely one cigarette. There is no acceptable threshold for smoking concerning the cardiovascular disease. To dramatically minimise their risk for such frequent serious diseases, smokers should strive to stop rather than reduce.